Tradition and Transition: The Journey of an iSchoolDeep in the Heart of Texas - Roy, Loriene; Simons, Rachel N. (DESIDOC Journal of Library & Information Technology, 2016)
The School of Information at the University of Texas at Austin (iSchool at UT-Austin) has evolved to be a unique program within the larger discipline of Library and Information Studies by incorporating traditional educational delivery while expanding the interdisciplinary nature of its faculty and curriculum. This article places our iSchool’s experiences within the narrative of the iSchool movement and points to various aspects of change, loss, and opportunity within the school’s history. The past and present status of both the graduate and undergraduate curricula at the iSchool at UT-Austin is described. We offer this story of the UT-Austin iSchool’s development as an example that helps deepen an understanding of the impact of such programs and their transformations on their students and faculty, as well as on the field of Library and Information Science (LIS).